2019
DOI: 10.1080/13880209.2019.1674342
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial mechanism of oridonin against methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: Context: Methicillin-resistant Staphylococcus aureus (MRSA) is a very harmful bacterium. Oridonin, a component in Rabdosia rubescens (Hemsl.) Hara (Lamiaceae), is widely used against bacterial infections in China. Objective: We evaluated oridonin effects on MRSA cell membrane and wall, protein metabolism, lactate dehydrogenase (LDH), DNA and microscopic structure. Materials and methods: Broth microdilution and flat colony counting methods were used to measure oridonin minimal inhibitory concentration (MIC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…When the OD 600 of the cultures reached 0.3, the bacteria were sub-cultured, and thymol was added at final concentrations of 0, 8, 16, 32 and 64 µg/mL. These subcultures were incubated with continuous shaking (190 rpm), or under static conditions at 37 • C. At various time points, the OD 600 of a 0.5 mL aliquot was measured on an ultraviolet-visible (UV-VIS) spectrophotometer (UNICO, Shanghai, China) [51].…”
Section: Growth Curve and Checkerboard Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…When the OD 600 of the cultures reached 0.3, the bacteria were sub-cultured, and thymol was added at final concentrations of 0, 8, 16, 32 and 64 µg/mL. These subcultures were incubated with continuous shaking (190 rpm), or under static conditions at 37 • C. At various time points, the OD 600 of a 0.5 mL aliquot was measured on an ultraviolet-visible (UV-VIS) spectrophotometer (UNICO, Shanghai, China) [51].…”
Section: Growth Curve and Checkerboard Assaysmentioning
confidence: 99%
“…It is a component of the essential oils extracted from various plants in the Lamiaceae, Verbenaceae, and Scrophulariaceae families, and it exhibits anti-inflammatory, antioxidant and potent antimicrobial properties [22][23][24]. In our previous studies [25] we showed the potent effects of thymol against MRSA infections. Thymol inhibits bacterial growth by altering the membrane permeability and disturbing both protein synthesis and binary fission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oridonin could also decrease the OVA-induced airway hyper-responsiveness and eosinophil number, and suppress the eosinophilia and mucus production, which confirms its great prospect in the treatment of asthma ( Wang S. et al, 2016 ). In addition, oridonin could effectively ameliorate inflammation-induced bone loss in the model of mice by inhibiting DC-STAMP expression ( Zou et al, 2020 ), halt the growth of methicillin-resistant Staphylococcus aureus (MRSA) ( Yuan et al, 2019 ), mitigate visceral hyperalgesia in a rat model of postinflammatory irritable bowel syndrome ( Zang et al, 2016 ), and augment gamma-globin expression in erythroid precursors from patients ( Guo et al, 2020 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…Lastly, the presence of extracellular DNA was studied as an indicator of cell membrane disruption. To perform this determination we modified the previous protocols from Chen and Cooper (2002) and from Yuan et al (2019).…”
mentioning
confidence: 99%